2022
DOI: 10.1039/d2cp02256g
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectroscopy of phthalocyanine in a supersonic jet revisited

Abstract: Spectroscopic investigation of phthalocyanine in the gas phase has tremendously profitted from molecular beam spectroscopy. Isentropic expansion accomplishes to reduce the population of rovibrational states to the vibrational ground state...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…The S 1 –S 0 transition seems to be a b-type transition, which reveals the symmetry species of the excited electronic state. The spectra measured by supersonic jet experiments 27 show a similar structure to those measured in this study. However, they conclude that the transition is 90% a-type and 10% b-type, which is not consistent with our analysis.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The S 1 –S 0 transition seems to be a b-type transition, which reveals the symmetry species of the excited electronic state. The spectra measured by supersonic jet experiments 27 show a similar structure to those measured in this study. However, they conclude that the transition is 90% a-type and 10% b-type, which is not consistent with our analysis.…”
Section: Resultssupporting
confidence: 82%
“…Ab initio calculations of large molecules remain challenging because of the difficulty in constructing both the calculation method and basis functions 26 . It should be acknowledged that while this manuscript was undergoing peer review, the high-resolution spectroscopy of FBPc using a supersonic jet was reported 27 . They used a Pyrex nozzle to prevent thermal decomposition of FBPc.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 , 10 , 18 ] The doubling of emission lines, absent in the gas phase, has been attributed to interactions with the surrounding helium layer. [ 15b ] Additionally, van der Waals clusters of H 2 Pc with Ar n ( n = 1–4) [ 13 , 19 ] and with H 2 O [ 10c,d ] have been formed through sequential pickup within the helium nanodroplets and subjected to spectroscopic analysis. In the case of the H 2 Pc‐H 2 O clusters, three isomeric complexes displaying different electronic excitation energies have been discussed.…”
Section: Introductionmentioning
confidence: 99%